2022
DOI: 10.1128/spectrum.00681-22
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for p53 during the HPV16 Life Cycle

Abstract: Human papillomaviruses are causative agents in around 5% of all cancers. There are currently no antivirals available to combat these infections and cancers, therefore it remains a priority to enhance our understanding of the HPV life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
(116 reference statements)
0
17
0
Order By: Relevance
“…p53 levels in HFK+HPV16 cells are detectable as E6 is spliced to E6* which removes the p53 degradation domain of E6 (28). We have demonstrated abundant p53 expression in HPV positive head and neck cancer cell lines and patient derived xenografts, as well as in primary keratinocytes immortalized by the entire HPV16 genome (29). No p53 is detectable in the HFK+E6E7 cells as E6 is not spliced and can therefore target p53 for proteasomal degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 levels in HFK+HPV16 cells are detectable as E6 is spliced to E6* which removes the p53 degradation domain of E6 (28). We have demonstrated abundant p53 expression in HPV positive head and neck cancer cell lines and patient derived xenografts, as well as in primary keratinocytes immortalized by the entire HPV16 genome (29). No p53 is detectable in the HFK+E6E7 cells as E6 is not spliced and can therefore target p53 for proteasomal degradation.…”
Section: Resultsmentioning
confidence: 99%
“…E6 expression certainly degrades p53 but in cells immortalized by the full genome E6 can be spliced to E6* which removes the ability to degrade p53 (28). Recently we demonstrated robust p53 protein expression in HFK+HPV16, in HPV16 positive head and neck cancer cell lines, and in HPV16 positive head and neck cancer patient derived xenografts (29). Overexpression of full length E6 in HFK+HPV16 cells abrogated their growth (an E6 mutant unable to degrade p53 did not) suggesting that p53 may be important for the HPV16 life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38] Indeed, among interaction with other viral proteins, p53 interacts with the C-terminal domain of E2 protein from high-risk HPVs. [20][21][22][39][40][41] Considering that the mechanism involved in the interplay between HPV E2 and p53 has not yet been elucidated, we decided to address the nature of the interaction between the two proteins, based on the initial mapping in transient transfection experiments. 21 We used the HPV16 C-terminal DNA-binding domain of E2 (E2C), and a rationally designed stability mutant of the full-length protein, previously described as pseudo wild-type p53.…”
Section: Resultsmentioning
confidence: 99%
“…19 Moreover, a very recent study showed that disruption of p53-HPV16 E2 interaction attenuates cell growth and blocks the viral life cycle. 40 Given p53 0 s features, its ability to undergo spontaneous LLPS is not surprising. These include modularity, oligomerization, nucleic acid between HPV E2 and p53 in the context of LLPS.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study represent one of likely many examples of a single virus targeting the same host molecule through multiple mechanisms. For example, Human Papillomavirus targets TP53 through independent mechanisms involving both the E6 and E7 proteins (Fontan et al, 2022). Likewise, poxviruses target caspase activity through multiple mechanisms (Nichols et al, 2017).…”
Section: Discussionmentioning
confidence: 99%